Black Experiences in Drury’s Fairview: Identity and Racial Tensions (Journal of the College of Languages (JCL), 2025)
This paper considers how black experiences are formed by identity and racial tensions reflected in the play "Fairview" by Jackie Sibblies Drury. The concept of identity will be the starting point of the discussion in relation to membership of social groups. The paper thereafter turns to the question of identity, mainly with respect to ethnicity, gender, and race, showing how the whole understanding of African-American culture and literature has been couched within the question of identity because of historical segregation and oppression. The study is built on three axis; the first axe shows the necessity for white people to deal with racism. The second axe concerns the power complexities with white viewership and the need for white creatives to realize their blind spot. The third axis examines the meta-theatrical elements of the play that present a critique toward traditional theatrical representations of black experiences. The paper will then turn to an examination of the multifaceted themes of identity and racial tensions in the play: what exactly is the difficulty that the characters have in reconciling real and perceived identities, and just how far Keisha goes in asking her audience to switch racial roles. The paper brings out the minute details of the rich complexities surrounding identity and racial dynamics expounded in the play.